2009
DOI: 10.1177/1088767909349749
|View full text |Cite
|
Sign up to set email alerts
|

Homicide Patterns and Public Housing: The Case of Louisville, KY (1989-2007)

Abstract: This study examines the impact of the revitalization of low-income, public housing properties on homicide patterns. It tracks the movement of homicide clusters from the initial properties to those neighborhoods where public housing residents were displaced over a 19-year period in Louisville, Kentucky. The median-income level of residents and vacant housing emerged as important predictors of homicide clusters. This article concludes that low-income public housing and Section 8 housing properties provide an env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Among numerous studies examining the associations between subsidized housing and crime, many researchers have also estimated the impacts of the Housing Choice Voucher (HCV) program on neighborhood crime in recent years (Ellen et al, 2012;Mast & Wilson, 2013;Popkin et al, 2012;Suresh & Vito, 2009). However, surprisingly few studies have focused on the relationships between LIHTC developments and neighborhood crime.…”
Section: Previous Evidence On Impacts Of Subsidized Housing On Neighbmentioning
confidence: 99%
“…Among numerous studies examining the associations between subsidized housing and crime, many researchers have also estimated the impacts of the Housing Choice Voucher (HCV) program on neighborhood crime in recent years (Ellen et al, 2012;Mast & Wilson, 2013;Popkin et al, 2012;Suresh & Vito, 2009). However, surprisingly few studies have focused on the relationships between LIHTC developments and neighborhood crime.…”
Section: Previous Evidence On Impacts Of Subsidized Housing On Neighbmentioning
confidence: 99%
“…Housing Policy Debate 555 more relevant to our work, in their assessment of public housing demolition and patterns of homicide concentration, Suresh and Vito (2009) also consider the concentration of HCV holders. They find that homicides are clustered in neighborhoods that also house voucher recipients, however, this work is purely cross-sectional and descriptive.…”
mentioning
confidence: 99%
“…Galster et al (2003) found no impacts from dispersed public housing or supportive housing on crime rates in Denver. Suresh and Vito (2009) focused on the voucher program and examined the spatial concentration of homicides before and after efforts in Louisville, KY, to deconcentrate public housing, primarily through HOPE VI and vouchers. They found that homicides moved to the parts of the city where public housing and voucher tenants moved, although their analyses were cross-sectional rather than longitudinal.…”
Section: Empirical Evidencementioning
confidence: 99%